Deindustrialization from the center perspective: US trade and manufacturing in the last two decades - Nikolaos Rodousakis; Giuliano Toshiro Yajima; George Soklis (Levy Economics Institute of Bard College, 2024)
We argue that the US trade and industry sector has experienced several unsustainable sectoral processes, including (i) a fall in the trade balance in machinery and equipment and high-tech (HT) industries, (ii) a rise in import multipliers in machinery and equipment and HT industries, (iii) a fall in the manufacturing share of GDP in machinery and equipment and HT industries, (iv) a rise in commodities share of GDP, (v) a fall in the wage share, (vi) structural shifts in the consumption share of wages, and (vii) a fall in employment multipliers for the US, particularly in manufacturing. To address these issues, the US must shift toward a more sustainable and valueadded economy with a focus on innovation and investment in high-tech industries, renewable energy, and sustainable agriculture. Additionally, policies must be put in place to address the negative impacts of resource extraction and to promote a more equitable distribution of income and wealth.
Keywords: C67; D57; O25; D33; 330; Input-Output Analysis; Industrial Policy; Income distribution